Repair of Surgical Defect by Pectoralis Major Flap Versus Free Radial Forearm Flap in Buccal Carcinoma: Assessment of Quality of Life - Hamid, Mohammad Abdul; Siddiquee, Belayat Hossain; Uddin, Md Mosleh; Razib, Syed Farhan Ali; Sohel, Shah; Jewel, Arif Mahmud (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Soft tissue reconstruction of the oral cavity is the most critical factor in achieving a successful functional result. Malignant lesions occurring in the buccal area are usually treated with primary surgical and/or radiotherapy of the head and neck region. Depending on the location and size of the buccal tumor, radical surgical treatment often affects all oral function such as speech, swallowing, chewing, oral rehabilitation, nutrition and appearance. To maximize postoperative function, flap repair is currently the preferred method for reconstruction of buccal defects after major surgery. Among the flaps most commonly used are pedicle pectoralis major myocutaneous flap and the free radial forearm fasciocutaneous flap. The choice of the best reconstructive option is still controversial. Objective: To find out the quality of life after repair of surgical defect by pectoralis major flap versus free radial forearm flap in buccal carcinoma. Methods: This prospective study was conducted in the department Otolaryngology- Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka from September 2017 to August 2019. A total number of 44 cases of buccal carcinoma patient who had the inclusion criteria were enrolled as a study sample. These subjects were selected from the Department of Otolaryngology-Head & Neck Surgery, Department of Oral & Maxillofacial Surgery, Bangabandhu Sheikh Mujib Medical University, Shahbag, National Institute of ENT, Tejgaon, Dhaka. Comparison of nominal or ordinal variables between patients who have undergone surgery with either the RFFF or PMMF were analyzed using a chi-square test. The UW-QOL scores were compared for each domain using the nonparametric Mann-Whitney test. P-value < .05 was accepted as the level of significance. Results: In this study 40 out of 44 patients were completed UW-QOL questionnaires. The median age was 52 (range 40-65years), the male-female ratio was 1.44:1. All were habituated in either smoking or betel leaf/ nut or alcohol. Most of them were illiterate to the primary level of education and suffering from stage- iii tumor. All these variables were statistically insignificant except gender. Patients reconstructed with RFFF felt better in shoulder domains than PMMF but felt worse appearance domains and these were statistically significant in both 3 months and 6 months postoperatively. Conclusion: The study result had shown that reconstruction of the defect after buccal cancer resection using either RFFF or PMMF significantly influences patient’s quality of life. This study will provide valuable information for surgeons who will decide reconstruction modalities for buccal cancer and also will help the patients getting a better outcome. Bangladesh J Otorhinolaryngol 2023; 29(1): 32-38